Assessing the utilization of palm oil mill effluent in photovoltaic and biogas hybrid energy system for off-grid village - Hiendro, Ayong; Husin, Fitriah; Junaidi, Junaidi; Khwee, Kho Hie (Institute of Advanced Engineering and Science, 2024)
The increasing demand for electricity, high prices, and lack of fossil fuels are forcing local community to look for renewable energy sources. Villages in palm oil mills have large volumes of biomass waste, especially palm oil mill effluent (POME), which causes environmental and health issues. This study proposed a hybrid renewable energy system consisting of solar photovoltaic (PV) and biogas to provide sustainable electrification for an off-grid village. To minimize the environmental impact and availability of the applied technology, the PV panels were incorporated with a biogas-fueled generator. Simulation experiments were carried out using the HOMER software for an average daily demand of about 159.65 kWh/day and a peak load of 20 kW. The investigation was emphasized to find the optimal PV/biogas system to serve the village community considering electrical, economical, and environmental aspects. Subsequently, a standalone biogas system was used as the base case. The proposed configuration consisted of a biodigester, a biogas-fueled generator, PV panels, an inverter, and batteries with 8.5 hours of autonomy to produce electricity of around 67,216 kWh/year. The results demonstrated the technical and economic feasibility, as well as the environmental benefits of a PV/biogas system for generating electricity for the off-grid village community.